Contextualizing Conceptions of Corruption: Challenges for the International Anti-corruption Campaign - Malte Gephart (German Institute of Global and Area Studies (GIGA), 2009)
While in an initial legal and academic anti-corruption wave corruption itself was at the center of analysis, research is now increasingly focused on anti-corruption discourse and praxis. The latter analyses have generated numerous criticisms of anti-corruption activities and anti-corruption research, and these are presented in this literature review. These criticisms range from the anti-corruption norm's legitimacy deficit, to the difficulty of defining and measuring corruption, to the discourse's depoliticization through its technicalization. The anti-corruption movement faces particular difficulties with respect to the tension between the universality of the anti-corruption norm and its simultaneous contextualization for specific and local application. This tension is especially important because it touches upon the central issues of the respective political communities, such as the division of the private from the public, which differ from one cultural context to another. The contextualization of anti-corruption concepts has to be enabled in various areas: first, with respect to the culturally shaped conception of the division between the public and the private; second, with respect to local understandings of corruption, that is, what is actually meant when talking about 'corruption'; and third, with respect to the low socioeconomic development levels in some countries, which do not permit the absence of corruption (evading a zero-tolerance rhetoric). – – Korruptionsverständnis kontextualisieren: Herausforderungen für internationale Anti-Korruptionskampagne. Während in einer ersten völkerrechtlichen und akademischen 'Anti-Korruptionswelle' Korruption selbst im Zentrum der Betrachtung stand, wird zunehmend der Korruptionsund Anti-Korruptionsdiskurs und die damit verbundene Praxis untersucht. Die Analysen haben viele Kritikpunkte hervorgebracht, die in diesem Literaturbericht zusammengefasst werden. Sie reichen von der mangelhaften Legitimation der Anti-Korruptionsnorm und - Programme, über die Schwierigkeit, Korruption zu definieren und zu messen bis hin zur Entpolitisierung des Diskurses durch seine Technisierung. Die internationale Anti- Korruptionsbewegung (deren Konzeption und Durchsetzung) ist zudem mit besonderen Schwierigkeiten in Bezug auf die Universalisierung der Anti-Korruptionsnorm und der gleichzeitigen Kontextualisierung dieser Norm für die spezifische, lokale Anwendung konfrontiert. Die Kontextualisierung ist jedoch gerade in Bezug auf Korruption von zentraler Bedeutung, da sie zentrale Fragen u. a. der jeweiligen politischen Gemeinschaft berührt. Sie muss in verschiedenen Bereichen ermöglicht werden: erstens in Bezug auf das kulturell geprägte, kontingente Verständnis zur Trennung von Privatem und Öffentlichen; zweitens in Bezug auf lokale Korruptionsverständnisse, d.h. was mit 'Korruption' eigentlich gemeint ist und drittens in Bezug auf sozioökonomische Niveaus, die die Abwesenheit von Korruption erst ermöglichen (weg von einer 0-Tolerance-Rhetorik).
Keywords: 300; corruption; anti-corruption; global governance; norms; cultural specificity; local implementation; Korruption; Kriminalpolitik; Nord-Süd-Beziehungen; Welt